2014
DOI: 10.1016/j.shaw.2014.06.001
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Knowledge Gaps Regarding Healthcare Workers' Exposure to Antineoplastic Drugs: Review of Literature, North America versus Europe

Abstract: We have been examining the issue of healthcare workers' exposure to antineoplastic drugs for nearly a decade and have observed that there appears to be more publications on the subject matter originating from Europe than from North America. The concern is that findings from Europe may not be generalizable to North America because of differences in handling practices, regulatory requirements, and training. Our objective was to perform a literature review to confirm our observation and, in turn, identify gaps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 79 publications
1
6
0
2
Order By: Relevance
“…Particularly, studies conducted in Asia showed the highest pooled ES compared with studies conducted in the Americas and even more in Europe. As suggested by Hon et al, different standard procedures, protocols, level of education, and legislations across the globe might influence the level of occupational risk, and consequently the conclusions drawn from one country might not be fully applicable to another [50]. Furthermore, in the cumulative analysis by year of publication, the results remained stable until 2008, while from 2009, they started to lose significance, with a large 95% CI.…”
Section: Discussionmentioning
confidence: 92%
“…Particularly, studies conducted in Asia showed the highest pooled ES compared with studies conducted in the Americas and even more in Europe. As suggested by Hon et al, different standard procedures, protocols, level of education, and legislations across the globe might influence the level of occupational risk, and consequently the conclusions drawn from one country might not be fully applicable to another [50]. Furthermore, in the cumulative analysis by year of publication, the results remained stable until 2008, while from 2009, they started to lose significance, with a large 95% CI.…”
Section: Discussionmentioning
confidence: 92%
“…While the research on surface and biological monitoring for ADs has continued with enthusiasm, demonstrated by the number of recent publications reporting improved technology for wipe [23][24][25] and urine [26][27][28] sampling, only a limited number of the studies published consider both matrices [11,13,29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dermal wipe samples do not account for other potential routes of occupational exposure such as inhalation or ingestion and, therefore, may not provide a complete measure of exposure. Given this, a number of occupational exposure studies have collected urine samples as a biomarker to estimate the dose of antineoplastic drug as evidenced in reviews conducted by Suspiro and Prista (2011) and Hon et al (2014a).…”
Section: Introductionmentioning
confidence: 99%